Effects of physicochemical properties of different substrates on characters and yield of maize - Yang, Wei (Emirates Journal of Food and Agriculture, 2018)
A reasonable method was used to analyze the effects of different substrates on the characters and yield of maize, and to improve the quality and yield of maize. The effects of the maize characters and yield of national Fluvo-aquic soil fertility and fertilizer efficiency monitoring base were analyzed from 6 aspects: fertilization and combined application, fertilization and density coupling, controlled release fertilizer (CRF), fertilization level, fertilization depth and proportion, and the amount of organic manure (chicken manure). Data processing is done by using Excel2003 and SPSS17.0 software, and multiple comparisons are made by using Duncan’s new multiple range test method. The experiment of the influence factor of fertilization and combined application shows that the combination of NPK+ organic fertilizer (constant and high) can increase maize character ratio and NPK+ high-amount organic manure can increase maize yield. The experiment of the influence factor of fertilization and density coupling shows that the maize characters reached the optimum under the condition of high fertilizer. The yield of maize is highest when the density is 60000 plants /hm2 and the amount of fertilizer is 10.71kg, 3.57kg and 8.93kg per 667m2. The experiment of the influence factor of controlled release fertilizer shows that the characters of CRF V and CRF VI are the best. The control time of CRF III, CRF V, CRF VI, and CRF IV compound fertilizer is long, which can increase maize yield. The experiment of the influence factor of fertilizer level shows that the best character of maize is achieved by using the controlled release fertilizer of Agricultural University 450 kg/hm2 and two-topdressing 600 kg/hm2. In the process of corn production, the use of A-40 treatment (Volfertile controlled release fertilizer 600kg/hm2) and the one-time application of base fertilizer can increase the yield of maize. The experiment of the influence factor of fertilization depth and proportion show that the best combination is that seed fertilizer 20% urea, 40% diammonium phosphate and potassium sulfate were applied under the surface of 8cm and base fertilizer 40% urea, 60% diammonium phosphate and potassium sulfate were applied under the surface of 16cm. It can improve the character and yield of maize at the same time. The experiment of the influence factor of organic manure (chicken manure) shows that the amount of organic fertilizer (chicken manure) 26923kg per hectare with fertilizing 35kg per plot is the best amount of fertilizer, and the yield of maize increases. The proposed method can comprehensively and accurately analyze the effects of different substrates on the character and yield of maize, which can promote rational fertilization in maize and improve the quality and yield of maize steadily.